Board-level employee representation in the Visegrád countries. (September 2019) - Zybała, Andrzej
This article addresses the complexity of trade-union approaches to board-level employee representation in the Visegrád countries, and the barriers it faces in particular national settings. Trade unionists in these countries accept the relevance of such employee representation in theory, but their practical agenda covers other issues which they perceive as more important as they struggle to survive at many levels of activity, and face growing existential uncertainty and risk. Unions also lack capacity to overcome obstacles such as reluctance on the part of the political class and managerial hostility to board-level representation; they cannot exert influence on major policy decisions at national level. They are operating in a more and more difficult environment, reflecting not merely a declining membership base, but also the recent economic crisis that failed to change the economic policy paradigm in the Visegrád countries: policies there still rely on a neoliberal approach and hence are not conducive to labour participation. What can still be seen as the predominant model is the traditional one of the market economy in which rights of ownership reign supreme.